Thermal transport during thin-film argon evaporation over nanostructured platinum surface: A molecular dynamics study. Issue 2 (June 2018) - Hasan, Mohammad Nasim; Shavik, Sheikh Mohammad; Rabbi, Kazi Fazle; Mukut, Khaled Mosharraf; Alam, Md. Muntasir
Investigation of thermal transport characteristics of thin-film liquid evaporation over nanostructured surface has been conducted using molecular dynamics simulation with particular importance on the effects of the nanostructure configuration for different wall–fluid interaction strengths. The nanostructured surface considered herein comprises wall-through rectangular nanoposts placed over a flat wall. Both the substrate and the nanostructure are of platinum while argon is used as the evaporating liquid. Two different wall–fluid interaction strengths have been considered that essentially emulate both hydrophilic and hydrophobic wetting conditions for three different nanostructure configurations. The argon–platinum molecular system is first equilibrated at 90 K and then followed by a sudden increase in the wall temperature at 130 K that induces evaporation of argon laid over it. Comparative effectiveness of heat and mass transfer for different surface wetting conditions has been studied by calculating the wall heat flux and evaporative mass flux. The results obtained in this study show that heat transfer occurs more easily in cases of nanostructured surfaces than in case of flat surface. Difference in behavior of argon molecules during and after the evaporation process, that is, wall adsorption characteristics, has been found to depend on the surface wetting condition as well as on presence and configuration of nanostructure. A thermodynamic approach of energy balance shows reasonable agreement with the present molecular dynamics study.